2020
DOI: 10.1124/dmd.120.090878
|View full text |Cite
|
Sign up to set email alerts
|

NADPH-Independent Inactivation of CYP2B6 and NADPH-Dependent Inactivation of CYP3A4/5 by PBD: Potential Implication for Assessing Covalent Modulators for Time-Dependent Inhibition

Abstract: Pyrrolo [2,1-c][1,4]benzodiazepine dimer (PBD) has shown broad antitumor properties and potential as a therapeutic agent for cancers. During a routine drug-drug interaction assessment, it was found that PBD is a reversible inhibitor of CYP2C8 (IC 50 = 1.1 mM) but not CYP1A2, 2B6, 2C9, 2C19, 2D6, or 3A4/5. Additionally, PBD is a classic time-dependent inhibition (TDI) of CYP3A4/5, with >30-fold shift in IC 50 after a preincubation with NADPH. All other CYPs tested did not show evidence for TDI, but potent inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In case of pyrrolobenzodiazepine derivatives, the ADC database showed that one out of three pyrrolobenzodiazepine derivatives is not an inhibitor or inducer of CYP3A and P‐gp while the other two are not reported. A recent publication showed that in vitro CYP inhibitory profiles depend on the structure of pyrrolobenzodiazepine derivatives 29 . Additionally, the ADC database showed that the unconjugated pyrrolobenzodiazepine was not detectable in the systemic circulation for two out of three pyrrolobenzodiazepine‐containing ADCs, while for the third ADC, it was not reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of pyrrolobenzodiazepine derivatives, the ADC database showed that one out of three pyrrolobenzodiazepine derivatives is not an inhibitor or inducer of CYP3A and P‐gp while the other two are not reported. A recent publication showed that in vitro CYP inhibitory profiles depend on the structure of pyrrolobenzodiazepine derivatives 29 . Additionally, the ADC database showed that the unconjugated pyrrolobenzodiazepine was not detectable in the systemic circulation for two out of three pyrrolobenzodiazepine‐containing ADCs, while for the third ADC, it was not reported.…”
Section: Resultsmentioning
confidence: 99%
“…A recent publication showed that in vitro CYP inhibitory profiles depend on the structure of pyrrolobenzodiazepine derivatives. 29 Additionally, the ADC database showed that the unconjugated pyrrolobenzodiazepine was not detectable in the systemic circulation for two out of three pyrrolobenzodiazepine-containing ADCs, while for the third ADC, it was not reported. Consistently, phase I studies with three pyrrolobenzodiazepine-containing ADCs, namely rovalpituzumab tesirine, vadastuximab talirine, and SGN-CD70A, showed that unconjugated pyrrolobenzodiazepine was generally not detectable in the systemic circulation at tested clinical doses, even though the unconjugated pyrrolobenzodiazepine assays were sensitive in the range of 10-60 pg/mL.…”
Section: Risk-based Payload-mediated Ddi Strategymentioning
confidence: 99%
“…Briefly, a portion of HLMs in the final protein concentration of 0.28 mg/mL in 100 mM potassium phosphate buffer (pH 7.4) was pre-incubated with Triphala extract (12.5–125 ÎŒg/mL), gallic acid, ellagic acid or one of the CYP 1A2, 2C9, 2D6 and 3A4 inhibitors (as positive control), i.e., α-naphthoflavone (0.025–0.1 ÎŒM), sulfaphenazole (0.01–1 ÎŒM), quinidine (0.5–2 ÎŒM) and ketoconazole (0.002–0.2 ÎŒM), at 37 °C for 5 min. Then, the reaction was initiated by the addition of an NADPH (1.3 mM) in 100 mM potassium phosphate buffer pH 7.4 and each probe substrate for CYP isoform ( Kosaka et al., 2020 ). The mixture was further incubated at 37 °C for various intervals (30, 10, 20 and 15 min for the determination of CYP 1A2, 2C9, 2D6 and 3A4, respectively) and terminated by adding ice-cooled acetonitrile.…”
Section: Methodsmentioning
confidence: 99%
“…CYP2C19 and CYP3A inactivation kinetic experiments were performed as previously reported [ 34 – 36 ], with an inactivation group and an activity evaluation group. The final concentration of the organic solvent was <1% (v/v).…”
Section: Methodsmentioning
confidence: 99%